PEMBELAJARAN TEMATIK UNTUK MENYEIMBANGKAN KERJA OTAK KANAN DAN OTAK KIRI - ErlinLadyawati, ErlinLadyawati; Prayogo, Prayogo (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
Thematic study is an activity of an intregrated learning. Activity by intregrating various kinds of a learning materials in one theme so that it can give valueble experience to the students. The activities in this thesis describes the way of right brain and left brain work. This theses is done in the third classes of Elementary School with the